1997
DOI: 10.1111/j.1445-2197.1997.tb02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Surgery in the Elderly: An Audit of Surgery in Octogenarians

Abstract: Background: Morbidity and mortality rates are higher in elderly compared to younger patients undergoing colorectal cancer surgery. This study was undertaken to see whether this finding applied to all colorectal surgery in the elderly and if so to try to identify the determining factors. Methods: All patients undergoing colorectal surgery between 1975 and 1990 were entered into a computerized database. Patients were divided into two groups, those less than 80 years (< 80) and those 80 years and more (80+), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 10 publications
8
33
0
2
Order By: Relevance
“…In other series, complicated forms of the disease reached figures similar to our data, in patients aged 80 or above (5,6,14,18,20).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In other series, complicated forms of the disease reached figures similar to our data, in patients aged 80 or above (5,6,14,18,20).…”
Section: Discussionsupporting
confidence: 76%
“…The increase of female patients as a function of age is also found in other series and is explained by the higher life expectancy of women (15). As has been described previously (5,(16)(17)(18)(19)(20), more than 60% of patients aged 80 or older had associated comorbidities. Similarly, there was an increase in perioperative risk (ASA grade) with age.…”
Section: Discussionsupporting
confidence: 61%
“…In a multivariate analysis Petersen et al [29] identified anastomotic leak as a significant independent factor for local recurrence but found no significant effect of leak on survival rate. Further risk factors for leaks or increased morbidity and mortality rates have been identified to be smoking, alcohol abuse, and advanced age (>80 years) [30,31,32,33,34,35,36,37]. Isbister [34] found a mortality rate of 11.1% in patients older than 80 years, as compared with 3.6% in younger patients.…”
Section: Discussionmentioning
confidence: 96%
“…Wie eine Studie aus Neuseeland zeigte, muss bei (sehr) alten Patienten mit kolorektalen Erkrankungen prinzipiell von einer signifikant erhöhten Morbidität und Letalität ausgegangen werden, wenn man diese Patientenpopulation mit einer beliebig jüngeren vergleicht [9]. Die Todesfälle traten dabei überwiegend aufgrund von kardiopulmonalen Komplikationen in der postoperativen Phase ein und konnten nicht der kolorektalen Grunderkrankung oder einer unmittelbar chirurgischen Komplikation angelastet werden.…”
Section: Kolorektale Erkrankungenunclassified